A two-phase approach to the simulation of the combined isotope/salinity signal of marine ice - Tison, Jean-Louis; Khazendar, Ala; Roulin, Emmanuel (2001)
A modified boundary layer box diffusion model is used to simulate the production of the combined oxygen isotope/salinity signal of a body of marine ice. The final signal is considered to be the result of fractionation and segregation processes occurring first upon the formation of frazil crystals in suspension and second during their accumulation and consolidation due to the advancement of a freezing front. The model results are compared to oxygen isotope and salinity values in a 45-m marine ice core from the Nansen Ice Shelf, Antarctica. Parameters more suitable to the modeling of marine ice (as opposed to sea ice) are introduced and conclusions are drawn on the origin of the impurity characteristics of marine ice, including the still unresolved question of its anomalously low salinity. Copyright 2001 by the American Geophysical Union. SCOPUS: ar.j FLWIN info:eu-repo/semantics/published